Targeting cytokines in inflammatory bowel disease. - Neurath, Markus (Science Translational Medicine, 2022)
Targeting cytokines in inflammatory bowel disease (IBD) is a useful clinical approach. Potential therapies for IBD include regulatory T cell transfer to restore cytokine balance, blocking proinflammatory cytokines (e.g., IL-12 and IL-23) or their receptors (sIL-6R and IL-36R), or inhibiting signaling kinases (e.g., JAK). An emerging trend in IBD therapy is to combine several anti-cytokine agents simultaneously.
EVALuna2:540209